Environmental & architectural phenomenology. Vol. 18, issue 3 - (:unkn) unknown (Kansas State University. Architecture Department, 2007)
Vol. 18, No. 3, Fall 2007 (includes "citations received," overview of the Architecture and Phenomenology conference, and essays by Christine Rhone, David Wang & Sarah Wagner).
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals